Pemanfaatan Sisa Kulit Kayu sebagai Karbon Aktif dalam Pengolahan Air Lindi Industri Pulp and Paper - Rifqi Sufra; Latifah Latifah; Nurul Ajeng Susilo; Endi Adriansyah; Luki Anugrah Wati; Astri Yulia; M. Syaiful; Hariestya Viareco; Marhadi Marhadi; Muhammad Abdul Ghony; Peppy Herawati (Universitas Batanghari, 2023)
The pulp and paper industry produces the remaining bark as solid waste, where this solid waste pile when it rains will produce leachate that seeps into the ground, causing soil and groundwater pollution. This wood waste can be used as activated carbon (adsorbent) for leachate treatment. The research was divided into two stages, namely adsorbent production and leachate treatment. Production of activated carbon from bark (bark) was activated using a solution of NaOH and H2SO4 as an activator, with variations of bark (gr): activator (ml) = 20:100; 50:200; 70:300. The leachate adsorption process used activated carbon with a mass of 2.5 and 5 g for 30, 60 and 120 minutes. The lowest adsorbent water content was 0.87% activated using NaOH, and the lowest ash content 0.79% when activated with H2SO4. This is still in accordance with the SII standard No.0258-88. The best variation occurred when the addition of activated carbon which was activated using 5 grams of H2SO4 for 120 minutes caused the most significant decrease in COD value of 52%, and pH 7.32. From the variations in the activation of activated carbon adsorbents, the activation of acidic solutions is better in leachate treatment.